THE NATURE OF POLITICAL SPLITS: THE ROSE REVOLUTION - SULABERIDZE, Iury (CENTRAL ASIA AND THE CAUCASUS, 2007)
All revolutions—including those described by political scientists as Color Revolutions—share certain regularities and development cycles; all of them resolve contradictions in systems that have fallen behind the times; and all of them create new contradictions as the revolutionary wave moves onward. The Rose Revolution in Georgia was spearheaded against Eduard Shevardnadze’s regime, which political scientists described as a “crossbreed of democratic bureaucracy and oligarchy.” The system built by the “father of Georgian democracy” turned out to be the worst example of a Soviet successor state: it was ineffective, lacked self-sufficiency, and failed to meet the basic needs of post-Soviet society. Today the Rose Revolution, which ushered in an era of Color Revolutions across the post-Soviet expanse, has become a target of scholarly studies. It can be scrutinized from different angles; I have posed myself the task of identifying the crucial features that created the genotype of power obvious at a certain development stage. I have undertaken to outline the psychological field in which the Georgian power culture was born. Did the revolution reflect the cultural-political needs of Georgian society? Whose interests did it promote? What is preventing and what is assisting the achievement of a national consensus? The Rose Revolution carried out under the slogan “Georgia without Shevardnadze” was obviously staged to remove the architect of the defective system best described as a “failed state” from power. It was “the birds of Eduard’s nest,” the young reformers who for some time served the democratization façade, who finally brought down the system. They struggled against the “dual world outlook” and the “policy of double standards,” while social contradictions became more deeply entrenched, ethnopolitical conflicts continued to smolder, and partocracy usurped power based on property. Their efforts rallied all those displeased with the regime in a united “national movement” driven by a slogan that served the image of the younger part of the political elite. The rising generation of politicians skillfully tapped popular discontent with the Shevardnadze regime and the unfolding systemic crisis to escalate them into a revolution. Not only did the government’s weakness help to keep the revolution peaceful. The democratic reforms and the relatively free media had already created a suitable climate and enabled the opposition to make use of the Rustavi-2 TV channel and the press to discredit the regime. The democratic opposition leaders were trained in Belgrade, where the potential of velvet revolutions was first put to the test. The globalization ideologists used the foundations and NGOs they set up to channel money for financing the revolution, bribing officials, and bringing the government to its knees.1